Study On Breast Feeding Practices Among Postnatal Women In A Tertiary Care Hospital In South Indian City - DR.MASEER KHAN; DR.PAVAN KUMAR KULKARNI; ZEBUNNISA; DR.A.CHANDRA SEKHAR (International Journal of Pharma and Bio Sciences, 2012)
A hospital basedcross sectional study was designed to know knowledge,attitude and practices of Breast feeding among post natal women in post natal wards of tertiary care Hospital in south Indian city. Interview technique was used as a tool for collection of the data information. A total of 100 postnatal mothers were included in the study. Among them 22% were illiterates. Majority of the mothers (67%) were housewives.78% post natal women were living in joint families.55% of post natal women who had normal delivery answered that breast feeding should be given with in 1 hr of delivery 65, be given with in 4 hrs of caesarean section.Only 50% women said that colostrum feed should be given .50% of the women had received advice on breastfeeding during antenatal period.And in that, only 17% from a healthcare worker; so, it is reinforced that we require more policies to educate the mothers regarding breast feeding practices.